Patterns of Iranian celebrities' self-representation in the social network Instagram - Zahra Ardekani Fard; Neda Razavizadeh (مطالعات رسانه‌های نوین, 2020)
With the emerge of online social networks in recent years, the phenomenon of the extensive presence of Based on Gaffman's theory, celebrities use social networks as a front-end tool to offer their desired “self” to their audience. To this end, a comprehensive model of celebrity self-representations in the medium was presented through assessing self-representation patterns, methods and strategies.we selected 391 posts of Instagrams from the pages of the 5 most popular Iranian celebrities by targeted sampling. The results of qualitative content analysis on the samples obtained five self-representation patterns in their pages. These five patterns include the pattern of the representation of professional identity, the model of social activism representation, interacting patterns with the audience, the pattern of political activism and the pattern of representing everyday personal life. Each of the first three patterns contained different strategies for self-representation, which were described as sub-types. Five characters were obtained using semiotic interpretations and evaluating implicit implications of the patterns: being specific and popular; being belonged to ordinary level of society; being active and responsible; being approved and benevolent; and being intimate and popular. The five characters represent the celebrities as a reference group.